Association of Sports Practice in Childhood and Adolescence with Cardiac Autonomic Modulation in Adulthood: A Retrospective Epidemiological Study - Christofaro, Diego Giulliano Destro [UNESP]; Tebar, William R.; Mota, Jorge; Delfino, Leandro D. [UNESP]; Santos, Amanda B. [UNESP]; Ritti-Dias, Raphael M.; Fernandes, Rômulo A. [UNESP]; Ferrari, Gerson; Vanderlei, Luiz Carlos M. [UNESP] (Springer Nature, 2024)
Background: Practicing sports during childhood and adolescence provides benefits to cardiac autonomic modulation (CAM) at these stages of life. However, it is not known whether these benefits to CAM persist into adulthood. Therefore, the objective of this study was to analyze the association of early sports practice (sports practice in childhood and/or adolescence) with CAM in adult life, regardless of habitual moderate-to-vigorous PA. Methods: The sample of the present study consisted of 242 adults (141 women and 101 men; age: 41.99 ± 16.24). The assessment of CAM was performed using heart rate variability indices. Sports practice in childhood and adolescence was assessed using a questionnaire. The intensity of physical activity was assessed using accelerometry. To analyze the association between previous sports practice (childhood and/or adolescence) and CAM, the Generalized Linear Model was adopted, considering CAM indices as continuous variables and early sports practice as a 3-fold factor (no sports practice; sports practice in childhood or adolescence; and sports practice in both childhood and adolescence) adjusted by sex, age, socioeconomic condition, and moderate to vigorous PA. Results: Sports practice in childhood was associated with the average standard deviation of all normal RR intervals expressed in milliseconds (SDNN): β = 5.89; 95%CI: 0.25;11.52, and the standard deviation of the long-term intervals between consecutive heartbeats (SD2): β = 7.63; 95%CI:1.04; 14.23 indices. Sports practice in adolescence was associated in adulthood with the SD2 index: β = 7.37; 95%CI: 0.71;14.04. Sports practice in at least one of the periods (childhood or adolescence) was significantly associated with the square root of the mean square of the differences between adjacent normal RR intervals for a period of time expressed in milliseconds (RMSSD) (β = 8.86; 95%CI = 0.71;17.01), and the standard deviation of the instantaneous beat to beat variability (SD1) (β = 6.21; 95%CI = 0.45;11.97). Sports practice at both stages of life was significantly associated with better SDNN (β = 7.70; 95%CI = 1.16;14.23) and SD2 (β = 10.18; 95%CI = 2.51;17.85). Conclusion: Early sports practice was associated with better CAM in adulthood, independently of the current physical activity level. Based on these findings, sports practice is encouraged from childhood and adolescence, for benefits to CAM in adult life.
Keywords: Cardiovascular Health; Heart rate variability; Previous sports practice; Youth